The Implementation of Psychosocial Therapy on the Victims of Landslide Disaster in Banjarnegara Central Java Province, Indonesia - Meiti Subardhini (Asian Social Work Journal, 2020)
Anxiety, Stress and Trauma are psychosocial conditions and labels for people who have suffered from any disasters and they areperceivably traumatized and unable to rise up from their adversity. Therefore, psychosocial recovery through various ways, especially therapy, becomes an alternative healing treatment for them. This study was aimed to examine the extent to which the implementation of psycho-medical therapy especially cognitive and behavioral therapy for the victims of landslides disaster in Banjarnegara. It was required to analyze how the effectiveness of psychosocial therapy was for stress and trauma undergone by the victims of landslide disaster in Banjarnegara. In practice, nourishment and visualization techniques of cognitive approach became an option to carry out at an early stage through several meetings. Furthermore, technique of systematic desentization and task orientation into advanced techniques performed on the victims of landslide disaster also went through several meetings. The procedure of the technique was carried out by two stages that divide the application of cognitive and behavioral approaches.Assessment and therapy function turn out to be the factor considered in this research, that the occuring change can be observed from the research subject. This research used qualitative descriptive methodology based on action research study, which basically requires describing the application of various techniques in psychosocial therapy conducted on three persons (3) of disaster victims as the research subject. The results of this research will perceivably benefit the research subject, as well as for the enrichment and experience of clinical social workers in various settings in overcoming psychosocial problems.